E-books and Attention Management: Exploring Digital Distractions in Academic Reading among Private University Students in Bangladesh (IUBAT Review, 2026)
With the rapid shift from print to digital formats in higher education, e-books have become widely accessible, affordable, and convenient, yet they also introduce unique cognitive and technological challenges. This study investigates how Bangladeshi university students manage digital distractions while reading e-books for academic purposes and how these challenges impact their focus, comprehension, and academic performance. Using a qualitative descriptive design, data were collected through semi-structured interviews with 30 purposively selected undergraduate students from diverse disciplines at a private university in Bangladesh. Thematic analysis revealed four major types of distractions: device-based interruptions, context-based disruptions, multitasking-induced distractions, and a lack of emotional or physical engagement with digital texts. The study also examines the effects of these reading distractions on students’ reading performance and identifies the strategies students use to manage their attention in technology-driven environments. To cope with these difficulties, students used a range of self-regulation strategies, including disconnecting from the internet, using alternative reading devices, modifying their surroundings, and engaging with annotation tools. The findings indicate that while e-books expand access to academic materials, their effectiveness is constrained by digital distraction. The study argues that improving academic digital reading requires institutional and pedagogical support that fosters attention management, rather than merely increasing access to e-resources.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 283-305